Data of Nebivolol on oxidative stress parameters in hypertensive patients - Barroso, Helena C. [UNESP]; Graton, Murilo E. [UNESP]; Potje, Simone R. [UNESP]; Troiano, Jéssica A. [UNESP]; Silva, Lilian X. [UNESP]; Nakamune, Ana Cláudia M.S. [UNESP]; Antoniali, Cristina [UNESP] (Elsevier, 2022)
Oxidative stress is a key feature in hypertension, since reactive oxygen species are involved in all stages of cardiovascular diseases. Saliva is a body fluid that can be used to investigate alterations in the oxidative system with several specific advantages over blood. Nebivolol is a third-generation selective β1-adrenergic receptor antagonist that promotes vasodilation and has been shown to reduce oxidative stress in pre-clinical and clinical studies. The use of Nebivolol in different periods of treatment demonstrated that it is an efficient anti-hypertensive drug. We evaluated the oxidative stress biomarkers and the enzymatic and non-enzymatic antioxidant systems in saliva of hypertensive patients before and after the use of anti-hypertensive therapeutic doses of Nebivolol, since saliva can be used as an auxiliary tool to analyze parameters of oxidative stress.
Keywords: Human beings; Hypertension; Nebivolol; Oxidative stress